Analysis of Debt to Asset Ratio and Debt to Equity Ratio on Return on Assets in Hotel, Restaurant, and Tourism Sub-Sector Companies Listed on the Indonesian Stock Exchange - Wahyu Indah Mursalini; Esi Sriyanti; Sherli Septiana (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
The purpose of this study is to investigate the influence of debt-to-asset and debt-to-equity ratios on the return on assets of companies operating in the hotel, restaurant, and tourism sector that are publicly traded on the Indonesia Stock Exchange between 2020 and 2023. Using a sample of 88 data from 22 businesses in this subsector, the methodology used is a quantitative approach with correlation analysis. Literature review and documentation were used for data collection, while multiple linear regression, descriptive statistical tests, and hypothesis testing were used for data analysis. With a value of t-value -3.384 > t-table 1.987 and Sig. 0.001 < 0.05, so the research findings show that the Debt to Assets Ratio (X1) variable has a partial influence on Return on Assets (Y). Apart from that, if t-value 6.468 > t-table 1.987 and Sig. 0.016 < 0.05, then the Debt-to-Equity Ratio (X2) also influences Return on Assets (Y). These two factors simultaneously influence Return on Assets (Y), with Sig. 0.000 < 0.05 and f-value 22.010 > f-table 3.10. During the 2020–2023 period, the hotel, restaurant and tourism subsectors listed on the Indonesia Stock Exchange experienced a combined impact of 34.1% from the Debt to Assets Ratio (X1) and Debt to Equity Ratio (X2) on Return on Assets (Y).